Давньоруське оборонне будівництво у працях М. П. Кучери - Моця, О.П. (Археологія, 2017)
У роботі аналізується внесок відомого вітчизняного дослідника Михайла Петровича Кучери у вивчення традицій давньоруського оборонного будівництва (міста, замки, Змійові вали). Mykhailo Petrovych Kuchera, a famous scholar of Kyiv Rus period antiquities, during his whole scientific activity, studied, first of all, fortification traditions of the autochthonous population of the south of Eastern Europe at the end of the 1st and the beginning of the 2nd millennia AD and conducted direct archaeological research at the sites of that period on the territory of modern Ukraine. Above all it concerned the urban centres’ defences, as well as lower social range settlements. One more direction in his scientific activity was the study of so called Zmiiv ramparts, a system of wooden and soil fortifications of the late 1st and the early 2nd millennia BC situated on the lands of the Dnipro River middle regions along 950 km in latitudinal direction and aimed in defending the autochthonous agricultural population in their standing against the warlike nomads of the Black Sea north region. Михаил Петрович Кучера — известный исследователь древностей эпохи Киевской Руси — на протяжении всей своей научной деятельности, в первую очередь, изучал традиции фортификации автохтонов юга Восточной Европы конца І — начала ІІ тыс н. э. и проводил непосредственные археологические исследования памятников того времени на территории современной Украины. Главным образом, это касалось укреплений урбанизационных центров, а также населенных пунктов более низшего социального ранга. Еще одним направлением его научной деятельности явилось изучение так называемых Змеевых валов — системы дерево-земляных укреплений конца І — начала ІІ тыс н. э. расположенных на землях Среднего Поднепровья на протяжении 950 км в широтном направлении и предназначенных для защиты автохтонов-земледельцев в их противостоянии воинственным кочевникам Северного Причерноморья.